2008
DOI: 10.1128/aem.00049-08
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Hard-To-Culture Subsurface Mercury-Resistant Bacteria and Discovery of New merA Gene Sequences

Abstract: Mercury-resistant bacteria may be important players in mercury biogeochemistry. To assess the potential for mercury reduction by two subsurface microbial communities, resistant subpopulations and their merA genes were characterized by a combined molecular and cultivation-dependent approach. The cultivation method simulated natural conditions by using polycarbonate membranes as a growth support and a nonsterile soil slurry as a culture medium. Resistant bacteria were pregrown to microcolony-forming units (mCFU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 29 publications
1
48
1
5
Order By: Relevance
“…Total numbers of bacteria in the soils were determined by acridine orange (AO) direct counting (27). Briefly, a 1:10,000 dilution of 1 g soil in 9 ml sterile Milli-Q water was filtered onto 0.2-m polycarbonate membranes (25 mm in diameter; Nuclepore), and at least 400 bacteria per sample were counted.…”
Section: Samplingmentioning
confidence: 99%
“…Total numbers of bacteria in the soils were determined by acridine orange (AO) direct counting (27). Briefly, a 1:10,000 dilution of 1 g soil in 9 ml sterile Milli-Q water was filtered onto 0.2-m polycarbonate membranes (25 mm in diameter; Nuclepore), and at least 400 bacteria per sample were counted.…”
Section: Samplingmentioning
confidence: 99%
“…It was long thought that Hg was relatively immobile in the subsurface due to sorption on sediment components such as iron oxides (1), but this assumption has come under scrutiny, since Hg has been unexpectedly found in groundwater at numerous sites, such as the Kirkwood-Cohansey aquifer in New Jersey (15, 16), the Waquoit Bay near Cape Cod, MA (17), and the coasts of California, northern France,. One attractive hypothesis to explain the mobilization of Hg in the subsurface is that bacteria reduce sediment-bound Hg(II) to Hg(0), possibly catalyzed by MerA.Several lines of evidence have indicated that Alphaproteobacteria are active in Hg-and uranium-contaminated sediments (22)(23)(24)(25). We have developed Xanthobacter autotrophicus Py2 (26) as a model system to study mer function in soil Alphaproteobacteria.…”
mentioning
confidence: 99%
“…Esta situación ocurre debido a que relativamente la baja diversidad genética de las comunidades microbianas se aclimata a la presencia del mercurio e induce un cambio en la composición de las mismas comunidades (RASMUSSEN et al, 2008). Además, la tolerancia al mercurio en las comunidades microbianas aclimatadas, varía en respuestas a las diferentes concentraciones del metal en los diferentes ambientes.…”
Section: Resultados Y Discusiónunclassified